Should larger reserve holdings be more diversified? - Roland Beck; Sebastian Weber (European Central Bank (ECB), 2010)
The notable increase in international reserve holdings over the past decade and their use during the global financial crisis of 2008/2009 has sparked renewed interest in the analysis of the optimal level of reserve holdings, in particular in countries which are subject to sudden stops. Less attention has been given to the optimal composition of reserves and even less to the joint determination of level and composition. In light of current developments, we show that despite the common belief that higher reserve levels should go along with higher diversification to minimize the opportunity costs from holding reserves, the opposite may even be true. It depends on the factors that stand behind the increase in reserves whether increased diversification is optimal or not. We estimate for a panel of 20 countries the determinants of the currency composition of reserves and show how it is affected by the different motives of reserve accumulation. In line with the recent literature on reserve levels we find that reserve accumulation is primarily driven by precautionary motives, which in turn underpins the allocation of reserves to safe assets. While we find primarily evidence of the allocation being a function of precautionary motives, we also find some weak evidence for reserve accumulation to lead to more diversified portfolios if reserve accumulation is driven by other factors than precautionary motives.
Keywords: F31; F33; E42; G11; 330; currency composition; Precautionary Motives; reserve accumulation; Währungsreserven; Portfolio-Management; Finanzkrise; Welt